Validating the Suicide Behavior Questionnaire-Revised among Filipino adults during the COVID-19 pandemic. Issue 2 (7th February 2023) - Dizon, John Ian Wilzon T.; Mendoza, Norman B.; Mordeno, Imelu G.; Nalipay, Ma Jenina N.
Abstract: The study aimed to examine the validity of the Suicide Behavior Questionnaire-Revised (SBQ-R) among adult Filipinos experiencing severe depression symptoms during the COVID-19-related lockdowns in 2020. Results support SBQ-R's internal reliability. Confirmatory factor analyses supported SBQ-R's one-factor structure and its measurement invariance across gender and age. The SBQ-R's positive relationship with negative affect and its negative relationships with positive affect and family support demonstrate the questionnaire's criterion-related validity. The SBQ-R's cutoff of ≥8 shows that 78% of the sample were at-risk for suicide. The SBQ-R is valid in assessing suicide risk among severely depressed adults during the COVID-19 pandemic.